Legal Counseling on Promiscuity Among Adolescents from the Perspective of the Juvenile Criminal Justice System Law in Mtsn 1 Palangka Raya City - Hairiana, Rizky; Jaitun, Almas; Amalya A., Atiqah; Amelia, Lia; Selvia, Vega; Hidayati, Sri; Salmah, Salmah; Setiarno P., Luthfi (PT FORMOSA CENDEKIA GLOBAL, 2025)
Community service through legal counseling aims to increase students' understanding of the dangers of promiscuity and introduce Law No. 11 of 2012 concerning the Juvenile Criminal Justice System (SPPA Law) in MTsN 1 Palangka Raya City. Promiscuity among adolescents has a significant negative impact, including the risk of involvement in criminal acts. The methods used include implementation methods and activity methods, namely planning, implementation, and evaluation through pretest and posttest to measure effectiveness. The results showed an increase in students' understanding from the majority of low categories (81.7%) to high (73.3%) after counseling. This counseling not only increases knowledge but also equips students with an understanding of the law to create a positive social environment and prevent them from risky behaviors.